Physiological demands of women`s rugby union: time-motion analysis and heart rate response - Virr, J. L.; Game, A.; Bell, G. J.; Syrotuik, D. (Journal of Sports Sciences, 2014)
The aim of this study was to determine the physical demands of women`s rugby union match play using time-motion analysis and heart rate (HR) response. Thirty-eight premier club level female rugby players, ages 18-34 years were videotaped and HRs monitored for a full match. Performances were coded into 12 different movement categories: 5 speeds of locomotion (standing, walking, jogging, striding, sprinting), 4 forms of intensive non-running exertion (ruck/maul/tackle, pack down, scrum, lift) and 3 discrete activities (kick, jump, open field tackle). The main results revealed that backs spend significantly more time sprinting and walking whereas forwards spend more time in intensive non-running exertion and jogging. Forwards also had a significantly higher total work frequency compared to the backs, but a higher total rest frequency compared to the backs. In terms of HR responses, forwards displayed higher mean HRs throughout the match and more time above 80% of their maximum HR than backs. In summary, women`s rugby union is characterised by intermittent bursts of high-intensity activity, where forwards and backs have similar anaerobic energy demands, but different specific match demands.